Synthetic Cells Synthesize Therapeutic Proteins inside Tumors. Issue 9 (28th December 2017) - Krinsky, Nitzan; Kaduri, Maya; Zinger, Assaf; Shainsky‐Roitman, Janna; Goldfeder, Mor; Benhar, Itai; Hershkovitz, Dov; Schroeder, Avi
Abstract: Synthetic cells, artificial cell‐like particles, capable of autonomously synthesizing RNA and proteins based on a DNA template, are emerging platforms for studying cellular functions and for revealing the origins‐of‐life. Here, it is shown for the first time that artificial lipid‐based vesicles, containing the molecular machinery necessary for transcription and translation, can be used to synthesize anticancer proteins inside tumors. The synthetic cells are engineered as stand‐alone systems, sourcing nutrients from their biological microenvironment to trigger protein synthesis. When pre‐loaded with template DNA, amino acids and energy‐supplying molecules, up to 2 × 10 7 copies of green fluorescent protein are synthesized in each synthetic cell. A variety of proteins, having molecular weights reaching 66 kDa and with diagnostic and therapeutic activities, are synthesized inside the particles. Incubating synthetic cells, encoded to secrete Pseudomonas exotoxin A (PE) with 4T1 breast cancer cells in culture, resulted in killing of most of the malignant cells. In mice bearing 4T1 tumors, histological evaluation of the tumor tissue after a local injection of PE‐producing particles indicates robust apoptosis. Synthetic cells are new platforms for synthesizing therapeutic proteins on‐demand in diseased tissues. Abstract : Synthetic cells contain all the nanoscale molecular machines and building blocks necessary for carrying out transcription and translation, including ribosomes, RNA polymerase, amino acids, and energy. Based on synthetically‐encoded DNA, the particles synthesize diagnostic and therapeutic proteins in tumors.